ANALISIS DESAIN SAMPUL BUKU AJAR BAHASA INDONESIA KELAS 1 SD: ANALISIS DESAIN SAMPUL BUKU AJAR BAHASA INDONESIA KELAS 1 SD - Zihan Usman; Hariyanto S. Auna (Jurnal Ilmu Pendidikan dan Budaya, 2023)
Textbooks are books that are used as standard books compiled for learning purposes. One of the textbooks used is an Indonesian language book with the theme “Accounts Can” which is used at the 1st grade elementary school level. This book is one of the books compiled and prepared to implement the independence curriculum. This book is very suitable for students at the elementary school level. In addition, the function of textbooks is also a tool for educators in the learning process. This research was conducted with the aim of analyzing the book cover contained in the book cover illustration. This study uses a qualitative method. This prompted researchers to research on Indonesian language book cover illustrations. The researcher wants to examine how the cover illustration relates to the design principles contained in the Indonesian language book cover illustration seen from the shape of the illustration composition, color and typography.